Technology Entrepreneurship Project (ENT 600) : Fitbit Inc. / Mohammad Abdullah Hanan - Abdullah Hanan, Mohammad (2021)
Fitbit Inc. is a company located in San Francisco, California, known for its wearable fitness trackers. These trackers, available in several colors, sizes, and prices, can measure steps, calories, and distance, along with users’ overall progress. Fitbit has sold 20.8 million products to date, and as of 2014, has amassed $745.4 million in revenue. The company is currently the top fitness band maker in the world with around 69% of the total market share in revenue, Fitbit has surpassed competitors Garmin, Misfit, Jawbone, and Nike. Fitbit faces some key issues that threaten their strategic objectives. Their current strategy is to pursue a premium, differentiating positing in the U.S. market, by offering quality products that increase their customers’ willingness to pay. However, competitors are working hard to gain market share. The global fitness tracker industry is becoming saturated with new entrants due to relatively low barriers to entry, an attractive market, and non-proprietary technology. This is increasing buyer power, as consumers have a vast choice of fitness trackers with various features and price points. Another key issue is the threat of substitutes. Smartwatches with fitness tracking features and a wide range of other capabilities are gaining ground. Success of substitute products could eliminate the need for a fitness-specific device. Other than that, the company currently faces several threats, like increasing competition and litigation from competitors, along with several opportunities, like society's increased interest in health and fitness and growing consumer awareness of wearable fitness devices. Fitbit itself has strength in its marketing campaigns and varied product line; its weaknesses are increasing competition for skilled personnel and its issues with product quality. Fitbit’s current target market includes technology users with low motivation for exercise. The market is therefore segmented psychographically, by lifestyle. Fitbit’s current marketing mix is very strong. Its diverse, high quality fitness trackers are competitively priced at market. The company currently uses dual distribution, selling its trackers both online and through retailers. Its promotion has recently expanded, with both a successful television advertising campaign and a strong presence on social media.